Exploring the Enjoyment of the Intergenerational Physical Activity - Buonsenso, Andrea (J Funct Morphol Kinesiol, 2021)
Intergenerational physical activity could be a pleasant method to prevent elderly sedentary behaviors. The aim of this study is to provide a basis to develop an intergenerational physical activity between preschool children and elderly people. An assessing enjoyment three questionnaire survey was administered to 140 participants (aged 67.8 ± 9.1): the global physical activity questionnaire (GPAQ) assessing the sedentariness degree; the physical activity enjoyment scale (PACES-Q) assessing enjoyment for the physical activity usually practiced; the physical activity enjoyment scale (PACES-INT) assessing the enjoyment for a hypothetical intergenerational program. Successively, the sample was divided into subgroups based on age, gender, marital status, education, employment, sports background, sedentariness level and residential location. Four multichoice questions, aiming to have guidelines in organizing an intergenerational program, were used. A total of 44.3% of the sample found the physical activity practiced pleasant, whereas 81.5% enjoyed the intergenerational program (only 7.1% expressed a negative judgment). A separated one-way ANOVA showed significant differences in PACES-INT for gender, (p = 0.009), residential location, (p < 0.001) and employment (p = 0.004). About 80% of the sample would adhere to the intergenerational programs, despite the fatigue fear and logistic or family relationship problems.